2018
DOI: 10.1002/jsfa.8929
|View full text |Cite
|
Sign up to set email alerts
|

FTIR spectroscopy for prediction of quality parameters and antimicrobial activity of commercial vinegars with chemometrics

Abstract: The results indicated that FTIR could be used as a rapid method to estimate the antimicrobial activities, TPC, color and antioxidant activities of vinegars. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
4
20
1
2
Order By: Relevance
“…In the study by Sengun et al, the examined vinegars were bought from local markets and their exact preparation method was not provided. On the other hand, Kadiroğlu noted significantly higher antioxidant capacity in grape vinegars compared with our study, with values up to 420 mg TE/L [ 44 ], where the exact preparation of the examined vinegars was also not provided. The antimicrobial properties, as well as the antioxidant activity of grape vinegars, may be attributed to the presence of both polyphenolic compounds and organic acids [ 45 ] where apart from acetic acid, there are also others including citric acid, tartaric acid [ 46 ], gallic acid, chlorogenic acid, caffeic acid, syringic acid, and ferulic acid [ 47 ].…”
Section: Discussioncontrasting
confidence: 81%
“…In the study by Sengun et al, the examined vinegars were bought from local markets and their exact preparation method was not provided. On the other hand, Kadiroğlu noted significantly higher antioxidant capacity in grape vinegars compared with our study, with values up to 420 mg TE/L [ 44 ], where the exact preparation of the examined vinegars was also not provided. The antimicrobial properties, as well as the antioxidant activity of grape vinegars, may be attributed to the presence of both polyphenolic compounds and organic acids [ 45 ] where apart from acetic acid, there are also others including citric acid, tartaric acid [ 46 ], gallic acid, chlorogenic acid, caffeic acid, syringic acid, and ferulic acid [ 47 ].…”
Section: Discussioncontrasting
confidence: 81%
“…Pundir and Jain found that the MIC and MBC of acetic acid ranged from 0.5% to 1% (higher than the present study) for some bacterial strains of E. coli , S. aureus and Bacillus species. Antimicrobial activities of 18 vinegars were determined by Kadiroğlu, with grape‐based vinegars exhibiting higher antimicrobial activity against S. aureus , E. coli and P. aeruginosa ; however, there were no statistically significant differences among all of the vinegars using in the present study. The antimicrobial effectiveness of vinegars may be associated with not only the acetic acid concentration, but also other organic acids (Table ).…”
Section: Resultsmentioning
confidence: 54%
“…), melanoidins (high molecular weight), ligustrazine, etc., also affects the antimicrobial potential of vinegars [22,44,66,67]. All the above classes of antimicrobial compounds are found in cereal vinegars, although compounds such as polyphenols are more abundant in wine and fruit vinegars [22,68].…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%
“…For example, the antimicrobial effect of RV on the survival of E. coli, Salmonella enterica serovars Typhimurium, P. aeruginosa, and S. aureus has been demonstrated in vitro [36,68,81]. RV was more effective against S. aureus compared to other vinegars [36].…”
Section: Antimicrobial Propertiesmentioning
confidence: 99%